Temporal Analysis of Onion Prices in major Markets in India - Rajalaxmi, Amand; Gummagolmath, K.C. (Journal of Agricultural Extension Management, 2019)
In the last two decades, area and production of onion has increased,extending into non-traditional areas.However, there is a marginal increase in productivity. Price analysis of onion revealed that instability of the prices are high in domestic markets as observed in the last two decades period. On the contrary, in a few markets, a positive correlation between arrivals and prices of onion is witnessed indicating the existence of exogenous factors such as more number of traders operating during harvesting season for hoarding of the stock for onward sale in other markets. Price analysis of onion also revealed that there is a cyclic trend of sudden hike in the price of onion. Thus there is a need to curb the exorbitant price rise of onions by intervention of the government based on supply demand dynamics. There is also a need for strengthening the marketing information system and increasing of post-harvest management infrastructure for onion to resolve the issues related to onion supply chain in India, being the world’s second largest producer of onion.